2003
DOI: 10.1007/s00440-003-0308-9
|View full text |Cite
|
Sign up to set email alerts
|

A proof of Parisi’s conjecture on the random assignment problem

Abstract: An assignment problem is the optimization problem of finding, in an m by n matrix of nonnegative real numbers, k entries, no two in the same row or column, such that their sum is minimal. Such an optimization problem is called a random assignment problem if the matrix entries are random variables. We give a formula for the expected value of the optimal k-assignment in a matrix where some of the entries are zero, and all other entries are independent exponentially distributed random variables with mean 1. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
121
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(121 citation statements)
references
References 20 publications
0
121
0
Order By: Relevance
“…This was conjectured in [Coppersmith and Sorkin, 1999] and the first proof appeared in [Linusson and Wästlund, 2004]. There is also shown that for m = n = k this term can be written as…”
Section: Bounds For the Case Of An Exponential Distributionmentioning
confidence: 77%
“…This was conjectured in [Coppersmith and Sorkin, 1999] and the first proof appeared in [Linusson and Wästlund, 2004]. There is also shown that for m = n = k this term can be written as…”
Section: Bounds For the Case Of An Exponential Distributionmentioning
confidence: 77%
“…which was asymptotically proved by Aldous [2], and for finite N , independently, by Linusson and Wästlund [12] and by Nair, Prabhakar and Sharma [13]. Earlier, Parisi [14] had conjectured (8) based on simulations and Coppersmith and Sorkin [5] have extended the conjecture to partial assignments.…”
Section: The Random Assignment Problemmentioning
confidence: 93%
“…Aldous [Ald92,Ald01] made this mathematically rigorous through reasoning about a "Poisson weighted infinite tree". For finite values of n, Parisi [Par98] conjectured the expected cost to be n i=1 i −2 , Coppersmith and Sorkin [CS99] extended the conjecture to cheapest cardinality-k assignments in K m,n , and these results were proved simultaneously, by different methods, by Linusson and Wästlund [LW04] and Nair, Prabhakar and Sharma [NPS05]. A beautiful short proof was later found by Wästlund [Wäs].…”
Section: Introductionmentioning
confidence: 99%